A young Ethiopian woman inspires others in her community to make it at home - Tesfaye, Y.; Teshale, T.; Moges, A.; Girma, R.; Mekuria, Wolde; Smith, J.; Hallet, P.; Phimister, E. (International Water Management Institute, 2025)
After migrating three times, Senya started an irrigation-based vegetable farming business; today, she is a role model for young people in her rural community to pursue domestic opportunities.